The Disaster Preparedness Program: a new model for sustainable capacity building through civil-military collaboration - Dr. G Oravec, MD; C Beadling, MD (Elsevier, 2015)
Background: The Disaster Preparedness Program (DPP) is a partnership between The Center for Disaster and Humanitarian Assistance Medicine (CDHAM)-a part of the Uniformed Services University of the Health Sciences-and the United States Africa Command (USAFRICOM). The DPP aims to assist African partner nations to enhance their disaster preparedness and response capabilities. The programme takes a whole-of-government approach to disaster preparedness and response, with an emphasis on plan development and, in some cases, creation of an autonomous national disaster management agency. Methods: The DPP worked with the Embassy and other US government stakeholders to identify key ministries involved in disaster preparedness. With DPP assistance, a technical team from the partner nation undertook a comprehensive assessment of their current disaster response capabilities. This information was used to construct a disaster management strategic work plan that identified specific gaps in disaster preparedness. A disaster simulation exercise was conducted with representatives from agencies and ministries involved in disaster response. They applied their existing structure, plans and resources to a scenario designed for their country by CDHAM in order to identify any additional shortfalls in the plan. The finalised work plan could then be used by the partner nation to prioritise and address immediate needs. Findings: Since 2009, CDHAM has worked with 16 partner nations. Ten countries have developed national pandemic influenza preparedness and response plans. By December, 2014, one country had used this plan to prevent the spread of Ebola, one country adapted this plan to a whole-of-government Ebola response, and six others are currently in the process of adopting this approach. Eight African armies have drafted "military support to civil authorities" disaster contingency plans, and one army has used this approach with Ebola. Ten countries have developed disaster management strategic work plans and are currently conducting activities in partnership with the US State Partnership Program, USAFRICOM, the Defense Threat Reduction Agency and the World Bank to fill gaps in their national disaster preparedness. Interpretation: Although the work with the DPP is expected to enhance partner nations' preparedness and response to disasters, measuring the outcomes of these projects may take several years. The next phase of the DPP will focus on sustained support to local programmes while working with them to assess improvements in their response capabilities. As a result of these successful partnerships, CDHAM is now also playing a major role in assisting west African partner nations with Ebola preparedness activities. Funding: Initially provided through USAID, but funding is now provided through the Defense Security Cooperation Agency's Overseas Humanitarian, Disaster, and Civic Aid.